Violence in the City of Women : Police and Batterers in Bahia, Brazil - Hautzinger, Sarah J., 1963- (Book collections on Project MUSE., 2007)
Brazil's innovative all-female police stations, installed as part of the return to civilian rule in the 1980s, mark the country's first effort to police domestic violence against women. This work explores this phenomenon as a window onto the shifting relationship between violence and gendered power struggles in the city of Salvador da Bahia.